COVID-19 pandemic impact on headache in healthcare workers: a narrative review - Romero, João Gabriel de Azevedo José; Salles-Neto, Franklin Teixeira de; Stuginski-Barbosa, Juliana; Conti, Paulo César Rodrigues; Almeida-Leite, Camila Megale (Headache Medicine, 2021)
Background: Pandemic of COVID-19, the potentially fatal disease caused by SARS-CoV-2, had caused intangible consequences on global health systems, economy, daily life, education, travel, leisure, work, and mental health. Its impact on mental and physical health, especially in health professionals, has been described. Objective: This study aimed to review and discuss the published evidence regarding the presence of headache on COVID-19 healthcare workers. Methods: In this review, we searched for all articles published in various data bases including PubMed / Medline, Scopus, and Web of Science and all original research studies, letters to editor, case reports, commentaries and reviews published in English, Portuguese or Spanish were searched. Two researchers independently analyzed published articles in order to include/exclude based on inclusion or exclusion criteria. Results: Thirteen articles were included. All studies included in this review were observational; eleven were cross-sectional studies, one was a prospective/cohort and one was a retrospective. Two studies evaluated psychological outcomes, mental health disorders and associated factors, one study investigated symptoms and causes of somatic symptom disorder and all other studies evaluated headaches associated with Personal Protective Equipment (PPI). Conclusions: The present review shows that COVID-19 pandemic has negative impact on physical and mental health in healthcare workers and headache has been associated to psychological stress and work overload during pandemic. Further studies are necessary to better investigate COVID-19 pandemic effects on headaches and other neurological conditions.